UJI EFEK ANALGETIKA EKSTRAK RIMPANG TEMU KUNCI (Boesenbergia pandurata (Roxb.) Schlechter PADA MENCIT JANTAN GALUR SWISS - Lina Winarti; Wantiyah Wantiyah (Faculty of Pharmacy, Universitas Gadjah Mada, 2011)
This research is conducted to evaluate analgetics effect of Boesenbergia pandurata (Roxb.) Schlechter extract using Witkin et al method. This method is conducted to see the elimination effect of pain after the administration of acetate acid by intraperitoneal injection to swiss furrow male mice. Pain effect by the administration of acetate acid causing stomach wall contraction, till the head and feet pulled rear and abdomen touch the cage room base. This symptom is named by writhing reflex and this symptom can be eliminated with an analgesic. Analysis was done by comparing the amount of writhe that happened after the giving of Boesenbergia pandurata (Roxb.) Schlechter extract with acetosal as positive comparator and aquadest as negative control. Writhing effect calculated during 30 minute after the administration of acetate acid by intraperitoneal injection. Boesenbergia pandurata (Roxb.) Schlechter extract between dose 15; 30 and 60 mg / kgBW have significant difference ( P<0.05). In the dose-effect relation it can be seen that more higher the dose give more higher effect. The amount of writhing in Boesenbergia pandurata (Roxb.) Schlechter extract dose 30 mg / kgBW not significantly differ with Acetosal, while Boesenbergia pandurata (Roxb.) Schlechter extract dose 15 mg / kgBW and 60 mg / kgBW have significant difference with Acetosal. Boesenbergia pandurata (Roxb.) Schlechter extract dose 15 mg / kgBB showing the amount of writhing larger than Acetosal and Boesenbergia pandurata (Roxb.) Schlechter extract dose 60 mg / kgBB has amount of writhing fewer than Acetosal. From the calculation of protection percentage administration significant difference between group. Boesenbergia pandurata (Roxb.) Schlechter extract dose 30 mg / kgBW and 60 mg / kgBW do not show significant difference with Acetosal. While from effectiveness percentage analysis also showing significant difference between group except Boesenbergia pandurata (Roxb.) Schlechter extract dose 30 mg / kgBW with Acetosal 130 mg / kgBW. So from overall of analysis resulting that analgetics activity of Boesenbergia pandurata (Roxb.) Schlechter extract start from dose 30 mg / kgBW have effective effect to reduce the pain induced with acetatic acid which equivalent with Acetosal as positive control. More great the dose give higher activity. From this research the dose of Boesenbergia pandurata (Roxb.) Schlechter extract 60 mg / kgBW have analgetics activity stronger than Acetosal